2019
DOI: 10.1038/s41598-019-44448-0
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone decreases gut permeability through upregulating occludin expression in primary human gut tissues and Caco-2 cells

Abstract: Progesterone plays a protective role in preventing inflammation and preterm delivery during pregnancy. However, the mechanism involved is unknown. Microbial product translocation from a permeable mucosa is demonstrated as a driver of inflammation. To study the mechanism of the protective role of progesterone during pregnancy, we investigated the effect of physiologic concentrations of progesterone on tight junction protein occludin expression and human gut permeability in vitro and syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 61 publications
(88 reference statements)
4
36
0
Order By: Relevance
“…For example, sex hormones such as estrogen and progesterone induced expression of TJ proteins and inhibited gut permeability in inflammatory organoid models from IBD patients and 2D cell line models. 200 Zhou et al 201 reported that progesterone upregulated OCLN expression in the gut and inhibited NF-κB activation to maintain gut barrier homeostasis. Irisin, a newly identified exercise hormone, was also reported to ameliorate gut barrier dysfunction via activation of the AMPK-UCP 2 pathway and binding to the integrin αVβ5 receptor.…”
Section: Treatment Strategies Against Gut Barrier Dysfunctionmentioning
confidence: 99%
“…For example, sex hormones such as estrogen and progesterone induced expression of TJ proteins and inhibited gut permeability in inflammatory organoid models from IBD patients and 2D cell line models. 200 Zhou et al 201 reported that progesterone upregulated OCLN expression in the gut and inhibited NF-κB activation to maintain gut barrier homeostasis. Irisin, a newly identified exercise hormone, was also reported to ameliorate gut barrier dysfunction via activation of the AMPK-UCP 2 pathway and binding to the integrin αVβ5 receptor.…”
Section: Treatment Strategies Against Gut Barrier Dysfunctionmentioning
confidence: 99%
“…In contrast, progesterone upregulated the expression of TJ proteins occludin and zona occludens 2 in the epidermis, and this effect was canceled by E2 in ovariectomized FvB mice [88]. Progesterone upregulated the expression of occludin in human gut tissues and Caco-2 cells [89]. It is thus hypothesized that the TJ barrier might be restored by progesterone but impaired by E2, opposite to the SC barrier, though confirmative studies are required for its verification.…”
Section: The Effects Of Sex Hormones On the Skin Barrier (Table 1)mentioning
confidence: 99%
“…Progesterone, on the other hand, has been indicated to induce apoptosis and reduce cell membrane permeability that gives rise to decrease invasive potential [67]. This storied hormone has been reported to have a protective role in preventing in ammation during pregnancy by reducing of IL-6 and TNF-α, and by the recovery of antioxidant enzyme performance in some tissues [68]. Likewise, Emerging evidence has mentioned that androgen-depended pathways have also been known to plays an important role in the pathogenesis and progression of malignancies, prostate, breast, and ovarian cancers [69,70].…”
Section: The Function Of Ovarian Hormonesmentioning
confidence: 99%